Influence of spatial laser beam profiles on thermal-fluid transport during laser-based directed energy deposition. Issue 4 (4th July 2021) - Wu, Jiazhu; Ren, Song; Zhang, Yi; Cao, Yang; Zhang, Dabin; Yin, Cunhong
ABSTRACT: The effects of the two types of typical spatial laser beam profiles (SLBP), including the super-Gaussian profile (SGP) and Gaussian profile (GP), on the thermal-fluid transport during laser-based directed energy deposition (L-DED) were numerically investigated. Considering the laser-powder-pool coupling effect, a comprehensive heat transport model including an input source model, laser-powder coupling model and molten pool thermal-fluid transport model is established. It is found that the SLBP has an important influence on the temperature gradient at the solidification interface and the flow field. Compared with the GP, the temperature gradient at the solidification interface under the SGP is high. Because the Marangoni stress and fluid momentum are in opposite directions, the fluid velocity distribution on the molten pool surface presents an 'M' shape. The fluid velocity on the molten pool surface under the SGP is obviously different from that under the GP.